1990
DOI: 10.1021/bi00458a029
|View full text |Cite
|
Sign up to set email alerts
|

NMR determination of the orientation of the magnetic susceptibility tensor in cyanometmyoglobin: a new probe of steric tilt of bound ligand

Abstract: The experimentally determined paramagnetic dipolar shifts for noncoordinated amino acid side-chain protons in the heme pocket of sperm whale cyanometmyoglobin [Emerson, S. d., & La Mar, G. N. (1990) Biochemistry (preceding paper in this issue]) were used to determine in solution the orientation of the principal axes for the paramagnetic susceptibility tensor relative to the heme iron molecular coordinates. The determination was made by a least-squares search for the unique Euler rotation angles which convert t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
262
0
3

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(273 citation statements)
references
References 44 publications
(81 reference statements)
8
262
0
3
Order By: Relevance
“…Furthermore, both the axial histidines experience reasonably large hyperfine shifts, suggesting roughly similar interactions with the haem iron, in contrast to ferricytochrome b5, the only other bis-histidinyl haem protein for which the haem electronic structure has so far been published [33]. It has often been suggested that the orientation of the axial ligands has a major influence on the distribution of the unpaired electron [31,[33][34][35][36], but it seems that this influence is unimportant as far as functional properties of the protein are concerned, such as redox potential and electron-transfer kinetics [23]. The high symmetry of the unpaired-electron distribution observed in cytochrome c" agrees very well with the proposed perpendicular orientation of the imidazole planes [2].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both the axial histidines experience reasonably large hyperfine shifts, suggesting roughly similar interactions with the haem iron, in contrast to ferricytochrome b5, the only other bis-histidinyl haem protein for which the haem electronic structure has so far been published [33]. It has often been suggested that the orientation of the axial ligands has a major influence on the distribution of the unpaired electron [31,[33][34][35][36], but it seems that this influence is unimportant as far as functional properties of the protein are concerned, such as redox potential and electron-transfer kinetics [23]. The high symmetry of the unpaired-electron distribution observed in cytochrome c" agrees very well with the proposed perpendicular orientation of the imidazole planes [2].…”
Section: Discussionmentioning
confidence: 99%
“…First, a set of iron-centered, reference coordinates, x 0 , y 0 , z 0 , are generated from the crystal coordinates, and the dipolar shift expressed in terms of these (known) coordinates, r, y 0 , O 0 , as follows (1,4,5): Figure 1, with the heme normal serving as the z 0 axis, and x 0 , y 0 in the heme plane. The major magnetic axis, z, is tilted from the heme normal (z 0 ) by the angle b in Figure 1B, and the projection of this tilt on the x 0 , y 0 plane, given by the angle, a, defines the direction of tilt (Fig.…”
Section: Determination Of the Anisotropies And Orientation Of Cmentioning
confidence: 99%
“…The different orientation of the histidine ring with respect to the heme plane (the projection of the ring in the two average structures differs of about 10°) may only account for about 20% of this discrepancy. The major contribution is due to the strong dependence of such pseudocontact shift on the deviation of the zz axis from the normal to the heme plane (Emerson & La Mar, 1990). Such deviation is larger in the case of the S. cereVisiae protein.…”
Section: Magnetic Susceptibility Tensormentioning
confidence: 99%